The domestication of planning ideas – the case of Shared Space - Peters, Sebastian (FormAkademisk, 2017)
New planning ideas of diverse types, ranging from new design concepts to large-scale development policies, are inherently challenging because they involve changes to prevailing thought and practice. As they are passed on, though, they are subjected to translation, adjusting them to discourses prevailing in different contexts, and often resulting in conceptual distortion. This article seeks to contribute to the theorization of the translation of planning ideas, by proposing the concept of domestication as a means of understanding such distortion. An analysis of one such challenging idea - Shared Space - serves to illustrate this concept and assess its usefulness.